Nilai Tukar Petani sebagai Indikator Kesejahteraan Petani Kedelai di Kecamatan Pulokulon Kabupaten Grobogan - Kurniawan, Juli (Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the average exchange rate of soybean farmers and determine the factors that affect the exchange rate of soybean farmers in Grobogan Regency. The basic method used in this research is analytical descriptive. The research location was chosen purposively, namely in Pulokulon District, Grobogan Regency. The type of data used in this study is primary data from 50 respondent farmers. Analysis of the data used is multiple linear regression. The results showed that the Farmer's Exchange Rate (NTP) was 115% which indicated that the farmers were in a prosperous condition. All variables studied together have a significant effect on the exchange rate of soybean farmers in Grobogan Regency. The results of the t-test analysis showed that other farm income variables, farmer household food expenditures, non-farm income and non-food expenditures of farmers' households had a significant effect on the soybean farmer's exchange rate, while the variables of farmer age, education, number of farmer family members, and farm income individually does not significantly affect the exchange rate of farmers in Grobogan Regency. From the results of the t-test analysis, the function model of the exchange rate of soybean farmers in Grobogan Regency is Y = 59.418 + 0.381X1 – 2.319X2 + 7.276X3 + 1.077x10-5X4 + 4.498x10-6X5 –3.681 x10-6X6 - 3.656 x10-6X7 - 3,859x10-6X8. Based on the results of the study, suggestions that can be given are that it is necessary to provide counseling regarding increasing the productivity of other farming commodities and being able to maximize the use of the yard to plant vegetables and fruits for household consumption and to use fuel efficiently. Farmers can have a side job outside the agricultural sector such as being a laborer, trader, or other work so as to increase the household income of farmers. The government can provide assistance in the form of capital for farmers both to develop farming and other businesses with the hope that the income obtained by the community will increase so that the welfare of farmers will also increase. In relation to soybean farming, farmers should form partnerships with women farmer groups in selling soybeans.